Feasibility of high-dose tadalafil and effects on insulin resistance in well-controlled patients with type 2 diabetes (MAKROTAD): a single-centre, double-blind, randomised, placebo-controlled, cross-over phase 2 trial - Fryk, Emanuel; Rodrigues Silva, Vagner Ramon; Bauzá-Thorbrügge, Marco; Schmelz, Martin; Gan, Li-Ming; Strindberg, Lena; Jansson, Per-Anders (EClinicalMedicine, 2023)
Background - Phosphodiesterase-5 inhibitors exert positive vascular and metabolic effects in type 2 diabetes (T2D), but the effect on insulin resistance in T2D is unclear. - Methods - This randomised, double blind, placebo-controlled, two-period crossover trial was conducted at Sahlgrenska University Hospital (Gothenburg, Sweden). Men without apparent erectile dysfunction (age 40-70 years) and women (age 55-70 years, post-menopause) diagnosed with T2D between 3 months and 10 years, haemoglobin A1c (HbA1c) < 60 mmol/mol and a body mass index (BMI) 27-40 kg/m2 were enrolled. Participants were randomly assigned to one period of oral tadalafil 20 mg once a day and one period of placebo for 6 weeks, separated by an 8-week wash-out period. Placebo and tadalafil tablets were made visually indistinguishable and delivered randomized in two separate boxes for each participant. Both treatment periods ended with a glucose clamp, and measurements of body composition and metabolic markers in blood, subcutaneous and muscular interstitial fluid. The primary aim was to assess difference in whole-body insulin resistance after 6-weeks of treatment, determined after completion of the two study arms, and secondary aims were to study effects of tadalafil on pathophysiology of T2D as well as tolerability of high-dose tadalafil in T2D. Primary analysis was performed in participants with full analysis set (FAS) and safety analysis in all participants who received at least one dose of study medication. This trial is registered with ClinicalTrials.gov (NCT02601989), and EudraCT (2015-000573). - Findings - Between January 22nd, 2016, and January 31st, 2019, 23 participants with T2D were enrolled, of whom 18 were included in the full analysis set. The effect of tadalafil on insulin resistance was neutral compared with placebo. However, tadalafil decreased glycaemia measured as HbA1c (mean difference −2.50 mmol/mol, 95% confidence interval (CI), −4.20; −0.78, p = 0.005), and, further, we observed amelioration of endothelial function and markers of liver steatosis and glycolysis, whereas no statistically significant differences of other clinical phenotyping were shown. Muscle pain, dyspepsia, and headache were more frequent in participants on high-dose tadalafil compared with placebo (p < 0.05) but no difference between treatments appeared for serious adverse events. - Interpretation - High-dose tadalafil does not decrease whole-body insulin resistance, but increases microcirculation, induces positive effects in the liver and in intermediate metabolites, in parallel with an improved metabolic control measured as HbA1c. High-dose tadalafil is moderately well tolerated, warranting larger trials to define the optimal treatment regimen in T2D. - Funding - The Swedish Research Council, Swedish Diabetes Foundation, Novo Nordisk Foundation, the Swedish state under the agreement between the Swedish government and the county councils, the ALF-agreement, Sahlgrenska University Hospital funds, Gothenburg Society of Medicine, Eli Lilly & Company, USA, and Eli Lilly & Company, Sweden AB.